Are Amman Stock Exchange Investors Overconfident? - Abu Khalaf, Bashar Khaled; Hammash, Firas Y. (International Journal of Economics and Financial Issues, 2017)
This study highlights the factors that affect investors' overconfidence. Since the overconfidence is considered one of the major psychological traits that impact the investment decision in Amman stock exchange, the importance of this study emerge through the importance of the investment decision itself. Accordingly, this paper studies overconfidence and number of its originators through structured questionnaire. The six factors we focus on include experience, financial knowledge, academic qualifications, opinions of financial advisors, and past performance of the stock. We randomly manage to get 250 respondents' sample of ASE traders. The results indicate that the investor overconfident is significantly increased by experience and financial knowledge factors. Keywords: Overconfidence, Amman Stock Exchange (ASE), Behavioral finance, Experience, Financial knowledge. JEL Classification: E44